(3x-2)(2x+6)=0

Simple and best practice solution for (3x-2)(2x+6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-2)(2x+6)=0 equation:


Simplifying
(3x + -2)(2x + 6) = 0

Reorder the terms:
(-2 + 3x)(2x + 6) = 0

Reorder the terms:
(-2 + 3x)(6 + 2x) = 0

Multiply (-2 + 3x) * (6 + 2x)
(-2(6 + 2x) + 3x * (6 + 2x)) = 0
((6 * -2 + 2x * -2) + 3x * (6 + 2x)) = 0
((-12 + -4x) + 3x * (6 + 2x)) = 0
(-12 + -4x + (6 * 3x + 2x * 3x)) = 0
(-12 + -4x + (18x + 6x2)) = 0

Combine like terms: -4x + 18x = 14x
(-12 + 14x + 6x2) = 0

Solving
-12 + 14x + 6x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '2'.
2(-6 + 7x + 3x2) = 0

Factor a trinomial.
2((-3 + -1x)(2 + -3x)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3

Subproblem 2

Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667

Solution

x = {-3, 0.6666666667}

See similar equations:

| 9x-(8x+9)=9x-33 | | 30y+8=32 | | (2-x)(2+x)=0 | | 5=9x-8x+6 | | (7-x)(x^2+2x-3)=0 | | 6(6-4)=12y | | x+27=-52 | | x^2=128-8x | | 11x^2+2x=10 | | (7a^2-2a+6)-(-5a^2+3)=0 | | 3x+8(x-1)=0 | | -9.9-26.7=6.1-24.7r | | D^2+3d+4=0 | | 4x^2+7x+3=6 | | -9.9-26.7=6.1-24.7 | | (1.2x^5-5x^3-0.7)+(3.7x^5+3)=0 | | 2m^2-13m=0 | | 6overh=4 | | 8=6g-4 | | (x^2-4x-7)x(x^2-2x+5)= | | 22a=-a^2 | | y=5-x^2-x-9 | | (3x-5)*x=232 | | Ln(sin(x))= | | Y+3=2y^2 | | (7a^2-3a)-(5a^2-5a)=0 | | 3(x-21)+3(x-2)=27 | | (3x-5)*5=232 | | 2(x-5)=32x | | 15=10+5(x-4) | | 27x^2+8=0 | | x+35=-57 |

Equations solver categories